Grabbing parallel corpora from the web - Almeida, J. J. (2002)
Multilingual resources are useful for linguistic studies, translation, and many other tasks. Unfortunately, these resources are difficult to obtain and organize. In this document we describe a set of tools designed to help in the task of mining bilingual resources from the web, from a specific site, from a file system, from a list of URLs, or from a translation memory. As a design goal we intend to build tools that can be used both cooperatively (in pipeline) and also in a independent way.